Numerical modeling of bottom trawling-induced sediment transport and accumulation in La Fonera submarine canyon, northwestern Mediterranean Sea - Payo Payo, M. (2017)
Bottom trawling leads to recurrent sediment resuspension events over fishing grounds. Recent studies have shown how bottom trawling can drive seascape reshaping at large spatial scales and enhance sediment transport in submarine canyons, which subsequently impacts deep-sea ecosystems. Present knowledge on the transfer and accumulation of sediment flows triggered by bottom trawling is based on localized and infrequent measurements whilst a more complete picture of the process is needed. The present work focuses on the modeling of sediment transport and accumulation resulting from trawling activities in La Fonera submarine canyon, northwestern Mediterranean Sea, thus contributing to an improved assessment of trawling impacts. Based on mooring data within a canyon gully, we use an inverse model to retrieve the unknown time series of resuspension due to trawling over the fishing grounds. This resuspension is later used as forcing for the direct problem: we simulate trawling-induced flows through the canyon and provide a 3D visualization of potential trawling impacts on sediment dynamics, including the identification of the propagation patterns of sediments resuspended by trawling. Flows coming from shallower fishing grounds are funneled through canyon flank gullies towards the canyon axis, with part of the resuspended sediment reaching the continental rise out of the canyon across the open continental slope. Trawling-induced sediment flows promote sediment accumulation beyond the canyon mouth. Given the wide geographical distribution of bottom trawling, our results have far-reaching implications that go much beyond La Fonera submarine canyon. Our study represents a starting point for the assessment of the sedimentary impact of bottom trawling in deep continental margins.